Евроремонт квартиры и дома - Мосякин В. Н. (Клуб Семейного досуга, 2006)
Экземпляры: ЦБ (20170310) / Инвентарный номер: 53633 / Цена: 70.00 / Сис.шифр: 38.683 / Авт.знак: Е 24 / ГРНТИ: 67.17.23 / ББК: 38.683